2020
DOI: 10.1210/jendso/bvaa087
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Sex, and Sugar: Glucocorticoids and Sex-Steroid Crosstalk in the Sex-Specific Misprogramming of Metabolism

Abstract: Abstract Early-life exposures to environmental insults can misprogram development and increase metabolic disease risk in a sex-dependent manner by mechanisms that remain poorly characterized. Modifiable factors of increasing public health relevance, such as diet, psychological stress, and endocrine-disrupting chemicals, can impact glucocorticoid receptor (GR) signaling during gestation and lead to sex-specific postnatal metabolic derangements. Evidence from human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 246 publications
(279 reference statements)
0
20
0
Order By: Relevance
“…Indeed, adult males had impaired glucose tolerance but no changes of adiposity if exposed perinatally while they showed enhanced body weight, adiposity, and insulin resistance if exposed during adulthood [ 194 ]. Consistent with the distinct regulation of the adipose tissue by glucocorticoids in males and females, female mice exposed perinatally to TF showed enhanced systemic insulin sensitivity, reduced adiposity and normal hepatic gluconeogenesis [ 193 ]. However, others demonstrated that TF impacted mitochondrial metabolism but failed to demonstrate obesogenic effects of TF [ 195 ].…”
Section: Edcs Mimicking Sex Steroid or Altering Active Sex Steroidmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, adult males had impaired glucose tolerance but no changes of adiposity if exposed perinatally while they showed enhanced body weight, adiposity, and insulin resistance if exposed during adulthood [ 194 ]. Consistent with the distinct regulation of the adipose tissue by glucocorticoids in males and females, female mice exposed perinatally to TF showed enhanced systemic insulin sensitivity, reduced adiposity and normal hepatic gluconeogenesis [ 193 ]. However, others demonstrated that TF impacted mitochondrial metabolism but failed to demonstrate obesogenic effects of TF [ 195 ].…”
Section: Edcs Mimicking Sex Steroid or Altering Active Sex Steroidmentioning
confidence: 91%
“…In vitro experiments using the 3T3-L1 cell culture model demonstrated that TF had GR-agonist activities [ 130 ]. Moreover, perinatal exposure to TF showed sex-specific adverse effects on the adipose tissue [ 192 ] which may have epigenetic basis [ 193 ] at least in males (females had not been studied). Indeed, adult males had impaired glucose tolerance but no changes of adiposity if exposed perinatally while they showed enhanced body weight, adiposity, and insulin resistance if exposed during adulthood [ 194 ].…”
Section: Edcs Mimicking Sex Steroid or Altering Active Sex Steroidmentioning
confidence: 99%
“…The importance of this steroid hormone crosstalk was comprehensively described in a recent publication by Daniel Ruiz, Vasantha Padmanabhan, and Robert Sargis [ 4 ]. In their review, the authors focus on metabolic (mis)programming during fetal development, and discuss that early overexposure to glucocorticoids (either exogenous, or as a consequence of stress) can disrupt sex steroid action later in life.…”
mentioning
confidence: 99%
“…While much research focuses on androgens and estrogens, progesterone receptor signaling is often ignored but may in fact contribute to sex-differences in metabolism as well, as covered by Ruiz et al [ 4 ]. In fact, steroid hormone receptors—glucocorticoid, androgen, progesterone, and the mineralocorticoid receptors; and to a lesser extent the estrogen receptor-α and -β—are very similar in molecular structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation